An NHC-Catalyzed Cross-Benzoin–Esterification Sequential Reaction for the Synthesis of Trifluoromethyl-Substituted α,β-Unsaturated Esters - Zhao, Qian; Feng, Li-Ying; Huang, Wei; He, Xiang-Hong; Peng, Cheng; Han, Bo (Synlett, 2016)
Efficient preparation of synthetically important CF3-containing α,β-unsaturated esters is described using an NHC-catalyzed multicomponent reaction. This approach combines sequential NHC-mediated HOMO and LUMO activation to produce a C–C bond and C–O bond in a one-pot operation.
Keywords: organocatalytic reaction; multicomponent reaction; NHC catalysis; trifluoromethylated compounds; cross-benzoin; esterification